A Case Study of Using Role Play in Teaching Speaking at Islamic Elementary School Raudhlatus Shibyan - Indriyani, Kholifatul (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2025)
This study aims to find out how to use role play in teaching speaking in grade V students at Islamic Elementary School Raudhlatus Shibyan. This research used a qualitative approach with a case study type of research. The subjects of the study were English teacher and grade V students who participated in speaking learning activities using the role play method. The researcher collected data through three main instruments, namely interviews with English teachers, observation of the learning process in the classroom, and documentation in the form of teaching notes, photographs and student learning outcomes. After the data from interviews, observations, and documentation were collected, the researcher performed three main steps in analyzing them. First, data reduction was carried out, namely sorting out the information that had been collected through the results of teacher interviews, then selecting important parts related to the focus of the research. Second, data presentation is carried out, namely compiling important points of the data that have been selected earlier, so that the flow can be seen clearly. Finally, make a conclusion. With these steps, researchers can conclude that role play can indeed help students speak more boldly and be more active in learning English. The findings showed that role play is applied in three stages of learning: preparation, implementation, and evaluation.